2013
DOI: 10.4137/bmi.s11966
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Prognostic Markers for Knee Osteoarthritis by Serum Proteomic Analysis

Abstract: BackgroundAs osteoarthritis (OA) is a highly heterogeneous disease in terms of progression, establishment of prognostic biomarkers would be highly beneficial for treatment. The present study was performed to identify novel biomarkers capable of predicting the progression of knee OA.MethodsA total of 69 plasma samples (OA patients undergoing radiographic progression, n = 25; nonprogression, n = 33; healthy donors, n = 11) were analyzed by surface-enhanced laser desorption/ionization time-of-flight mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
(49 reference statements)
1
20
0
1
Order By: Relevance
“…Previous studies have suggested some biomarkers that can be utilized in the diagnosis, grading severity and, the prognosis of OA progression. Until now, despite intensive research, just a few biochemical factors, of which SF or serum levels reveal a correlation with the radiographic findings of OA patients, have been known . The biomarkers that have been specifically defined for OA can be related to bone, cartilage, and synovium metabolisms or systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested some biomarkers that can be utilized in the diagnosis, grading severity and, the prognosis of OA progression. Until now, despite intensive research, just a few biochemical factors, of which SF or serum levels reveal a correlation with the radiographic findings of OA patients, have been known . The biomarkers that have been specifically defined for OA can be related to bone, cartilage, and synovium metabolisms or systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…By SELDI-MS, they compared serum from a large OA cohort to those of healthy individuals and OA patients and they identified four novel markers for OA, including V65 vitronectin fragment, C3f peptide, CTAP-III, and m/z 3762 protein. Another OA proteomic study in plasma was reported by Takinami et al (2013). This group applied SELDI-MS to plasma samples from progressive OA, non-progressive OA, and healthy individuals without OA.…”
Section: Proteomic Analysis Of Serum In Oamentioning
confidence: 97%
“…In a subsequent study specifically focused in OA, the same authors identified four differential MS peaks Effect of IL-1b QConCAT + LC-MS/MS 252 Reduction of TIMP1 secretion [42] Characterization of MMPs and ADAMTs cleavage LC-MS/MS 16 Profiles of proteolytic peptides [44] Wounded zones of OA versus unwounded versus HC iTRAQ + LC-MS/MS 401 OPG, POSTN [37] OA versus HC articular cartilage vesicles LC-MS/MS 1700 big-H3, DEL1, VTN, HTRA1 [38] Chondrocytes Effect of IL-1b or TNF-a Antibody array 79 IL-8, IL-6, OPG [40] Effect of IL-1b or OSM Proteomic study of osteoarthritis Review informahealthcare.com between OA, RA and controls [11]. The same approach recently enabled the identification of potential prognostic markers for knee OA [47]. Finally, other kind of high-throughput proteomic approaches that have been performed using plasma or serum are protein microarrays, such as antigen microarrays or nucleic acid programmable protein arrays for profiling the autoantibody repertoire of OA [48].…”
Section: Proteomic Analysis Of Secretomes From Joint Tissues and Cellsmentioning
confidence: 98%
“…Finally, a recent work described the identification of putative biomarkers of psoriatic arthritis in SF using OA samples as control group [57]. Progressive versus non progressive OA SELDI 300 peaks APOC-I, APOC-III, TTHY fragment [47] OA K/L I/II versus K/L IV versus HC iTRAQ + LC-MS/MS 349 26 differential proteins [8] OA versus RA versus HC autoAb profiling Antigen and NAPPA arrays 3840 antigens Anti-CHST14 auto-antibodies [48] Serum and synovial fluid OA versus HC UF + LC-MS/MS 40 COL2, PRG4, SAA, TUB, VIME, MGP [50] MB + MALDI-TOF 61 peaks Two peptide peaks [55] Early and late OA versus HC 1-DE + LC-MS/MS 135 18 altered in OA [51] DIGE + SRM 337 AFAM, CLUS, LUMI, PEDF, ALS [56] PsA versus early OA LC-MS/MS + SRM 12 proteins quantified by SRM Apart from serum or SF, no other MS-based studies have been carried out for OA biomarker discovery in alternative body fluids, with the exception of the development of an immunoaffinity-LC-MS/MS assay for the determination of a type II collagen neoepitope in urine [58,59]. Being a promising strategy for the accurate quantification of markers in biofluids, this approach was more recently applied for the analysis of endogenous aggrecan fragments in SF and urine [60].…”
Section: Proteomic Analysis Of Secretomes From Joint Tissues and Cellsmentioning
confidence: 99%